Analysis of Adsorption Data of Nitrogen and Carbon Dioxide on Chemically-Activated Carbons from Cherry and Wild Cherry Stones by considering Different Approaches Based on Different Models - M.N. Alaya; M.A. Hourieh; F. El-Sejariah; A.M. Youssef (Adsorption Science & Technology)
Activated carbons were prepared by activation of cherry and wild cherry stones with phosphoric acid and zinc chloride. The adsorption of nitrogen at −196°C and of carbon dioxide at 0°C was followed and the data obtained analyzed through the use of models based on theories of surface coverage and micropore filling. Chemically-activated carbons obtained from cherry and wild cherry stones exhibited high surface areas and large total pore volumes. Most of the pores lay in the micropore region while a small fraction of the total surface area was located in non-micropores. Fair agreement was established on comparing the textural parameters derived from models based on the theory of surface coverage with those derived from the micropore filling theory. Micropores should be classified into ultrafine pores, micropores and super-micropores, such sub-division helping in the prediction of the adsorption behaviour and in the interpretation of the data derived therefrom.